Knowledge attitude and practices on prevention of anaemia among antenatal women - S., Ilamathi; G. K., Poomalar; M., Rajalakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Iron Deficiency Anaemia in pregnancy is associated with intra uterine growth retardation, pre term labour, low birth weight baby and it also increases maternal and perinatal mortality. Methods: This KAP study was conducted for six months. All the pregnant women attending the outpatient department of Sri Manakula Vinayagar medical college and hospital, were provided with a predesigned questionnaire by the principal investigator. Data was collected after obtaining consent from 167 patients regarding their knowledge, attitude and practices towards anaemia. Results: In our study we found that women with age more than 25 years, advanced gestational age, educated participants and women belonging to higher socio-economic status showed adequate knowledge about anemia and its complications. Conclusions: Health Education plays an important role, in creating awareness among antenatal women and by implementing this into practice will help in prevention of anaemia.